2010
DOI: 10.1371/journal.pntd.0000676
|View full text |Cite
|
Sign up to set email alerts
|

Computational Identification of Uncharacterized Cruzain Binding Sites

Abstract: Chagas disease, caused by the unicellular parasite Trypanosoma cruzi, claims 50,000 lives annually and is the leading cause of infectious myocarditis in the world. As current antichagastic therapies like nifurtimox and benznidazole are highly toxic, ineffective at parasite eradication, and subject to increasing resistance, novel therapeutics are urgently needed. Cruzain, the major cysteine protease of Trypanosoma cruzi, is one attractive drug target. In the current work, molecular dynamics simulations and a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 57 publications
2
53
0
4
Order By: Relevance
“…This view is based upon the observation that static Xray cysteine proteases structures, several in free form and complexed to inhibitors (mainly covalent inhibitors), show little differences in their conformation, as measured by the deviation of backbone dihedral angles (Laskowski & Qasim, 2000;Ratia et al, 2008;Gaspari, Varnai, Szappanos & Perczel, 2010). However, heteronuclear NMR (Lee et al, 2012) and molecular dynamics (MD) simulation (Capriles & Dardenne, 2007;Durrant, Keranen, Wilson & McCammon, 2010;Chaudhuri et al, 2011) studies have revealed that the irreversible covalent inhibitors in complex to the cysteine protease are flexible on the picoseconds-nanoseconds (ps-ns) time scale (Song & Markley, 2003;Clarkson & Lee, 2004;Gaspari et al, 2010;Hoelz et al, 2011;Hoelz et al, 2012;Meher, Kumar, Sharma & Bandyopadhyay, 2012;Kramer et al, 2014;Kunze et al, 2014).…”
Section: Figure 1 Herementioning
confidence: 99%
See 1 more Smart Citation
“…This view is based upon the observation that static Xray cysteine proteases structures, several in free form and complexed to inhibitors (mainly covalent inhibitors), show little differences in their conformation, as measured by the deviation of backbone dihedral angles (Laskowski & Qasim, 2000;Ratia et al, 2008;Gaspari, Varnai, Szappanos & Perczel, 2010). However, heteronuclear NMR (Lee et al, 2012) and molecular dynamics (MD) simulation (Capriles & Dardenne, 2007;Durrant, Keranen, Wilson & McCammon, 2010;Chaudhuri et al, 2011) studies have revealed that the irreversible covalent inhibitors in complex to the cysteine protease are flexible on the picoseconds-nanoseconds (ps-ns) time scale (Song & Markley, 2003;Clarkson & Lee, 2004;Gaspari et al, 2010;Hoelz et al, 2011;Hoelz et al, 2012;Meher, Kumar, Sharma & Bandyopadhyay, 2012;Kramer et al, 2014;Kunze et al, 2014).…”
Section: Figure 1 Herementioning
confidence: 99%
“…This work represents the first study using MD simulation in a time scale of 100 ns to investigate the conformational change involved in the inhibition mechanism of CRZ, an important therapeutic target for Chagas' disease (Capriles & Dardenne, 2007;Durrant et al, 2010;Rogers et al, 2012) …”
Section: Figure 1 Herementioning
confidence: 99%
“…Interestingly, the tested compounds were selected based on both their ensemble-average and ensemble-best performance, suggesting that ligands binding tightly to a smaller number of conformers should also be considered. In a third line of work, cruzain, a T. cruzi protease targeted for the treatment of Chagas disease was subjected to five 20 ns simulations [72]. Diverse structures from this ensemble have then been used in a hierarchical RCS approach to re-score promising NCI compounds, the best of which have been considered for forthcoming experimental validation.…”
Section: Previous Applications Of the Relaxed Complex Schemementioning
confidence: 99%
“…It has emerged that many such compounds would have been either missed or overlooked in a rigid receptor scheme, which only represents a narrow portion of the complex protein conformational landscape. Furthermore, applications of the RCS are extending beyond the discovery of lead compounds at known sites to the exposure of entirely novel druggable binding pockets and binding modes, as has been shown for influenza neuraminidase [78], GPCRs [56], HIV-1 protease [79] and T. cruzi cruzain [72]. …”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%
“…Besides the hydrophobic interactions, the residue Glu-205 at the bottom of the S2 subsite increases the interaction through hydrogen bonds with hydroxyl groups at C27 and C28. Studies have shown the importance of this residue Glu205 as a different target, when compared to others proteins of peptidase C1 family members 43 . Although papain and cruzain to be isostructural in the region of catalytic sites, different conformations was found for the inhibitor Cbz-Phe-Ala-FMK where there is a 60° rotation of Phe side chain in cruzain relative to papain 44 and too in the region of the loops and turns.…”
Section: Discussionmentioning
confidence: 99%